Pengaruh Pengungkapan Lingkungan, Sosial, Tata Kelola (LST), dan Inovasi Hijau terhadap Nilai Perusahaan - Shadra, Mutiara; Hutapea, Riauli Susilawaty (Indonesian Accounting Literacy Journal, 2024)
Attention to sustainability aspects, particularly through environmental, social, and governance (ESG) factors, is on the rise among shareholders. ESG disclosure is the process of providing information about a company's ESG performance to the public. In addition, companies can also increase their company value through green innovation. Green innovation is the process of creating new products, processes, or services that are more environmentally friendly. This study was conducted to analyze the effect of ESG disclosure and green innovation on firm value. This research is quantitative descriptive study using secondary data. The population is consumer goods companies listed on the Indonesia Stock Exchange during the period 2018-2022. The analytical technique used is a panel regression model, which was analyzed using the Eviews 13 program. The result of this study indicate the ESG disclosure has effect on firm value, while the green innovation has no effect on firm value.